Analisis sidik jari herba pegagan (Centella asiatica (L.) Urb) di daerah Jawa Barat menggunakan metode spektrofotometri FTIR kombinasi dengan PCA - Andriansyah, Ivan; Gumilar, Hasna Fadhilah; Yuliantini, Anne; Juanda, Dadang (Jurnal Agrotek Ummat, 2022)
Centella asiatica is a plant that has many benefits and is included in 50 types of medicinal plants that are often used as traditional medicine. Lack of quality control of traditional medicine can lead to a lot of fraud. A multi-component approach such as fingerprint patterns can be used for quality control of traditional medicinal raw materials. The purpose of this study was to determine the fingerprint pattern of Centella asiatica using the FTIR method combined with PCA. The method used is the measurement of the spectrum using FTIR at wave numbers 4000-650 cm-1 with a resolution of 4 cm-1. The fingerprint pattern of Centella asiatica in West Java obtained scores plot values of PC-1 against PC-2 81% (PC-1 45% and PC-2 36%) West Java Centella asiatica herbs cannot be in the same quadrant, Centella asiatica Sumedang area is in quadrant one, Bandung, Pangandaran and Sukabumi areas are in quadrant two and Bogor is in quadrant three. The validation of the PCA analysis showed a plot score of 73% (PC-1 44% and PC-2 29%) and the eigenvalues of PC-1 and PC-2 were 3.379 and 2.705, respectively. The FTIR method combined with PCA can classify each variabel from each plant by determining the number of selected main components. Obtained fingerprint profile of 96% ethanol extract of Centella asiatica herb in the area of West Java using FTIR obtained spectrum results from these 5 types of samples, combined with PCA. The fingerprint profile in the Score plot shows that Sumedang Centella asiatica has differences with the areas of Bandung, Bogor, Pangandaran, and Sukabumi.